Annual dynamics of wild bee densities: attractiveness and productivity effects of oilseed rape. Issue 5 (1st May 2015) - Riedinger, Verena; Mitesser, Oliver; Hovestadt, Thomas; Steffan-Dewenter, Ingolf; Holzschuh, Andrea
Abstract : Mass‐flowering crops may affect long‐term population dynamics, but effects on pollinators have never been studied across several years. We monitored wild bees in oilseed rape fields in 16 landscapes in Germany in two consecutive years. Effects on bee densities of landscape oilseed rape cover in the years of monitoring and in the previous years were evaluated with landscape data from three consecutive years. We fit empirical data to a mechanistic model to provide estimates for oilseed rape attractiveness and its effect on bee productivity in comparison to the rest of the landscape, and we evaluated consequences for pollinator densities in consecutive years. Our results show that high oilseed rape cover in the previous year enhances current densities of wild bees (except for bumble bees). Moreover, we show a strong attractiveness of and dilution on (i.e., decreasing bee densities with increasing landscape oilseed rape cover) oilseed rape for bees during flowering in the current year, modifying the effect of the previous year's oilseed rape cover in the case of wild bees (excluding Bombus ). As long as other factors such as nesting sites or natural enemies do not limit bee reproduction, our findings suggest long‐term positive effects of mass‐flowering crops on bee populations, at least for non‐ Bombus generalists, which possibly help to maintain crop pollination services even when crop area increases. Similar effects are conceivable for other organisms providing ecosystem services in annual crops and should be considered in future studies.